Assessing the Psychological Burden of Eco-Anxiety Among Urban Youth and the Therapeutic Role of Green Space Exposure for Public Health Interventions - Muhammad Alfathan Harriz; Bambang Eko Supriyanto; Sumaira Aslam (International Forum of Researchers and Lecturers, 2024)
This study investigates the effectiveness of green-space–based interventions in reducing eco-anxiety among urban adolescents, a population increasingly vulnerable to climate-related psychological distress. Eco-anxiety, characterized by persistent worry, cognitive overload, and emotional tension in response to environmental change, has emerged as a significant mental-health challenge. The intervention examined in this research involved structured exposure to natural environments combined with guided reflective activities over multiple sessions. Quantitative results showed a substantial reduction in eco-anxiety symptoms, with participants experiencing approximately a 30% decrease in climate-related worry after the intervention. Improvements were also observed in emotional resilience, including enhanced self-regulation, greater cognitive clarity, and improved coping capacity. Qualitative findings reinforced these outcomes, revealing that participants reported deeper emotional calm, stronger feelings of agency, and an increased sense of connectedness with nature. They described green spaces as restorative environments that helped reduce overthinking, clear mental fatigue, and create psychological grounding. These experiences appear to activate mental-restoration processes consistent with environmental psychology, suggesting that nature engagement can serve as both a preventive and therapeutic mental-health strategy. A comparison with conventional counseling approaches indicated that while standard psychological support aids emotional regulation, it often fails to address the specific ecological concerns driving eco-anxiety. In contrast, green-space exposure offers a more targeted and holistic benefit, combining physiological relaxation with meaningful emotional reassurance. The study concludes that expanding access to green spaces, incorporating nature-based therapeutic elements into public-health programs, and promoting balanced climate literacy may enhance adolescent well-being in a time of intensifying environmental challenges.